How Politics and Institutions Affect Pension Reform in Three Postcommunist Countries - Orenstein, A. Mitchell (The World Bank, 1999)
March 2000 - During reform's three phases - commitment-building, coalition-building, and implementation - there are tradeoffs among inclusiveness (of process), radicalism (of reform), and participation in, and compliance with, the new system. Including more, and more various, veto and proposal actors early in the deliberative process may increase buy-in and compliance when pension reform is implemented, but at the expense of faster and greater change. Orenstein examines the political and institutional processes that produced fundamental pension reform in three postcommunist countries: Hungary, Kazakhstan, and Poland. He tests various hypotheses about the relationship between deliberative process and outcomes through detailed case studies of pension reform. The outcomes of reform were similar: each country implemented a mandatory funded pension system as part of reform, but the extent and configuration of changes differed greatly. Countries with more veto actors - social and institutional actors with an effective veto over reform - engaged in less radical reform, as theory predicted. Poland and Hungary generated less radical change than Kazakhstan, partly because they have more representative political systems, to which more associations, interest groups, and proposal actors have access. Proposal actors shape the reform agenda and influence the positions of key veto actors. Pension reform takes longer in countries with more veto and proposal actors, such as Poland and Hungary. Legacies of policy, the development of civil society, and international organizations also profoundly affect the shape and progress of reform. Orenstein sees pension reform as happening in three phases: commitment-building, coalition-building, and implementation.